Efficacy and safety of chemical thromboprophylaxis in renal transplantation – A systematic review. Issue 192 (August 2020) - Kohli, Ruchika; Estcourt, Lise; Zaidi, Abbas; Thuraisingham, Raj; Forbes, Suzanne; MacCallum, Peter; Tan, Joachim; Green, Laura
Abstract: Introduction: The benefit of administering chemical thromboprophylaxis to chronic kidney disease patients undergoing renal transplantation is unclear and no previous systematic review has addressed this as reflected by variations in national guidelines. Methods: A literature search was performed using MEDLINE, Embase, Cochrane, CINAHL, World Health Organisation (WHO) International Clinical Trials Registry Platform and ClinicalTrials.gov databases to December 2019. Studies included participants undergoing renal transplantation only with no contra-indication to thromboprophylaxis, no history/clinical suspicion of acute organ rejection and those describing a form of chemical thromboprophylaxis intervention compared with another form, no intervention or placebo. Results: Thirteen studies with 1600 patients were included. There was wide variation concerning type of thromboprophylaxis, time of onset, dosing and duration. Reports of symptomatic/asymptomatic venous thromboembolism and mortality were limited. Seven studies reported on renal allograft thrombosis. When comparing thromboprophylaxis to no intervention, there was no evidence of difference for thrombosis risk (risk ratio 0.2; [95% CI 0.01–4.63]), however all studies were underpowered to answer this question. Six studies reported on major bleeding but type of intervention, timing of onset and duration of thromboprophylaxis varied significantly, making it difficult to pool data for further analysis. Conclusion: There is insufficient evidence to advise on efficacy and safety of chemical thromboprophylaxis in patients undergoing renal transplantation or to determine whether one chemical thromboprophylaxis is better than another thromboprophylaxis. Highlights: Patients with chronic kidney disease are at increased risk of thrombosis and bleeding. Chemical thromboprophylaxis may reduce the occurrence of renal allograft thrombosis. However, this is at the expense of increased risk of bleeding. Current quality of evidence is poor.